PENGARUH KOMPETENSI DAN PRESTASI KERJA PEGAWAI TERHADAP PROMOSI JABATAN PADA KANTOR KEMENTERIAN AGAMA KOTA PEMATANGSIANTAR - Novita, Weri; Lie, Darwin; Efendi, Efendi; Chandra, Erbin (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2019)
The result of this study can be concluded as follows: 1. Competence, job achievement of employee, and is good job promotion. 2. There is positive influence between competence and job achievement of employee, on job promotion. 3. There is moderately high correlation between competence and job achievement of employee with job promotion. Then good or not job promotion can be explained by the competence and job achievement of employee. 4. Hypothesis test results stated H0 rejected, meaning competence and job achievement of employee have a positive and significant impact on job promotion at Kantor Kementerian Agama Pematangsiantar City either simultaneously or partially.Keywords: Competence, Job Achievement of Employee, and Job Promotion